2016
DOI: 10.1017/s0022377816000222
|View full text |Cite
|
Sign up to set email alerts
|

Simplified variational principles for non-barotropic magnetohydrodynamics

Abstract: Variational principles for magnetohydrodynamics were introduced by previous authors both in Lagrangian and Eulerian form. In this paper we introduce simpler Eulerian variational principles from which all the relevant equations of non-barotropic magnetohydrodynamics can be derived. The variational principle is given in terms of five independent functions for non-stationary barotropic flows. This is less then the eight variables which appear in the standard equations of barotropic magnetohydrodynamics which are … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
52
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(52 citation statements)
references
References 41 publications
0
52
0
Order By: Relevance
“…Magnetic helicity is an invariant of MHD (e.g. Elsässer (1956), Woltjer (1958), Moffatt (1969Moffatt ( , 1978). In (1.7) it is assumed that the normal magnetic field component B n = B·n vanishes on the boundary ∂V .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic helicity is an invariant of MHD (e.g. Elsässer (1956), Woltjer (1958), Moffatt (1969Moffatt ( , 1978). In (1.7) it is assumed that the normal magnetic field component B n = B·n vanishes on the boundary ∂V .…”
Section: Introductionmentioning
confidence: 99%
“…which is just the circulation of the topological velocity along the magnetic field lines. This quantity can be written in terms of the generalized Clebsch representation of the velocity [18]:…”
Section: Metage Translationsmentioning
confidence: 99%
“…Yahalom & Lynden-Bell [4] has also shown that the translation group of the magnetic metage is connected to Woltjer [5,6] conservation of cross helicity for barotropic MHD. Recently the concept of metage was generalized also for non barotropic MHD in which magnetic field lines lie on entropy surfaces [7]. This was later generalized by dropping the entropy condition on magnetic field lines [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both conservation laws for the helicity in the fluid dynamics case and the barotropic MHD case were shown to originate from a relabelling symmetry through the Noether theorem [4][5][6][7]. Consider the equations of non-barotropic MHD [8,9]:…”
mentioning
confidence: 99%